Pengaruh Emotional Value, Perceived Quality, Perceived Price Terhadap Keputusan Pembelian Produk Private Label di MG Store Padang - Henryanto Abaharis; Karisma Julianti; Romi Susanto; Jhon Fernos (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effect of emotional value, perceived quality, and perceived price on the purchase decisions of private label products at MG Store Padang. This type of research is quantitative, with the research subjects being consumers who shop at MG Store Padang. The data collection technique used in this study is a questionnaire. The sampling technique is non-probability sampling with a sample size of 96 people. The results of the study indicate that emotional value (X1) has a positive and significant effect on the purchase decisions of private label products at MG Store Padang. In addition, the test results show that the variable perceived quality (X2) does not affect the purchase decisions of private label products at MG Store Padang. The test results also show that the variable perceived price (X3) does not affect the purchase decisions of private label products at MG Store Padang.